EFFECT OF ELF-EMF ON NUMBER OF APOPTOTIC CELS; CORRELATION WITH REACTIVE OXYGEN SPECIES AND HSP - (:unkn) unknown (AKADEMIAI KIADO ZRT, 2010)
It is by now accepted that extremely low frequency electromagnetic fields ELF-EMF (0-300 Hz) affect biological systems although the mechanism has not been elucidated yet. In this study the effect of ELF-EMF on the number of apoptotic cells of K562 human leukemia cell line induced or not with oxidative stress and the correlation with heat-shock protein 70 (hsp70) levels was investigated. One sample was treated with H2O2 while the other was left untreated. ELF-EMF (1 mT, 50 Hz) was applied for 3 hours. ELF-EMF alone caused a decrease in the number of apoptotic cells and a slight increase in viability. However, it increased the number of apoptotic cells. In cells treated with H2O2. hsp70 and reactive oxygen species (ROS) levels were increased by ELF-EMF. These results show that the effect of ELF-EMF on biological systems depends on the status of the cell: while in cells not exposed to oxidative stress it is able to decrease the number of apoptotic cells by inducing an increase in hsp levels, it increases the number of apoptotic cells in oxidative stress-induced cells.
Keywords: Extremely low electromagnetic fields (ELF-EMF); apoptotic cells; heat-shock protein70; oxidative-stress; K562; FREQUENCY ELECTROMAGNETIC-FIELDS; HEAT-SHOCK PROTEINS; MAGNETIC-FIELDS; NEUROBLASTOMA-CELLS; REDOX; EXPOSURE; HEAT-SHOCK-PROTEIN-70; HOMEOSTASIS; MODULATORS; MECHANISM